Characteristics of shock-induced boundary layer separation on nacelles under windmilling diversion conditions - Boscagli, Boscagli; MacManus, David G.; Tejero, Fernando; Sabnis, Kshitij; Babinsky, Holger; Sheaf, Christopher T. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The boundary layer on the external cowl of an aero-engine nacelle under windmilling diversion conditions is subjected to a notable adverse pressure gradient due to the interaction with a near-normal shock wave. Within the context of Computational Fluid Dynamics (CFD) methods, the correct representation of the characteristics of the boundary layer is a major challenge to capture the onset of the separation. This is important for the aerodynamic design of the nacelle as it may assist in the characterization of candidate designs. This work uses experimental data obtained from a quasi-2D rig configuration to provide an assessment of the CFD methods typically used within an industrial context. A range of operating conditions is investigated to assess the sensitivity of the boundary layer to changes in inlet Mach number and mass flow through a notional windmilling engine. Fully turbulent and transitional boundary layer computations are used to determine the characteristics of the boundary layer and the interaction with the shock on the nacelle cowl. The correlation between the onset of shock induced boundary layer separation and pre-shock Mach number is assessed and the boundary layer integral characteristics ahead of the shock and the post-shock recovery evaluated and quantified. Overall, it was found that the CFD is able to discern the onset of boundary layer separation for a nacelle under windmilling conditions.